The agriculture-nutrition nexus in Samoa - Lee-Hang, Desmond; Hatier, Jimmy; Francis, Judith Ann (Technical Centre for Agricultural and Rural Cooperation, 2016)
Agriculture, fisheries and tourism drive the small, open economy of Samoa, a small island nation in the south-west Pacific Ocean with a population of less than 200,000. The agricultural sector accounts for around one-tenth of gross domestic product (GDP), half of what it was in the 1990s. Remittances account for around one-fifth.